Deploying zone-based firewalls - Pepelnjak, Ivan (Cisco Press, 2006)
Deploying Zone-Based Firewalls (Digital Short Cut) Ivan Pepelnjak ISBN: 1-58705-310-1 Improved firewall policy configuration means network administrators can more easily understand the effect of firewall policies on network traffic. This functionality allows the grouping of physical and virtual interfaces into zones to simplify logical network topology. The creation of these zones enables the application of firewall policies on a zone-to-zone basis, instead of having to configure policies separately on each interface. With this functionality, configuration is easier to understand. Deploying Zone-Based Firewalls teaches you how to design and implement zone-based firewalls using new features introduced in Cisco IOS release 12.4T. This digital short cut, delivered in Adobe PDF format for quick and easy access, provides you with background information on IOS Firewall Stateful Inspection and Zone-based Policy Firewall configuration. The short cut then focuses on designing zone-based firewalls and deploying zone-based policies with the new Cisco IOS command-line interface (CLI). Common deployment scenarios are included to highlight proper use of this powerful Cisco IOS feature. Table of Contents: Chapter 1: Introduction to Zone-Based Firewalls Chapter 2: Typical Zone-Based Firewall Designs Chapter 3: Configuring Zone-Based Policy Firewalls in Cisco IOS Chapter 4: Case Study: Firewall with a Perimeter Network Chapter 5: Advanced Zone-Based Policy Firewall Configuration Chapter 6: Configuring Transparent Firewalls.